Deteksi Dini Burnout Akademik dan Gangguan Psikologis Remaja Menggunakan DASS-Y di SMA Wilayah Citra Raya - Dwiana, Alya; Santoso, Alexander Halim; Gunaidi, Farell Christian (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Adolescent mental health, including the phenomenon of academic burnout, has become a critical concern in post-pandemic educational settings. Burnout in teenagers is often triggered by academic pressure, social expectations, and unaddressed emotional burdens, which may impair academic performance and psychosocial well-being. This community service project aimed to conduct early detection of academic burnout and related psychological symptoms—stress, anxiety, and depression—among high school students in the Citra Raya area using the Depression Anxiety Stress Scales for Youth (DASS-Y). A total of 145 students participated in the screening using the 21-item DASS-Y questionnaire. The screening process was conducted collectively in the school setting, facilitated by the project team and school counselors. The results revealed that 15.2% of students experienced stress, 26.9% anxiety, and 24.8% showed depressive symptoms, ranging from mild to extremely severe levels—all of which are key indicators of academic burnout. Although the majority of students fell within the normal range, the presence of early psychological symptoms in a considerable proportion highlights the need for prompt intervention. In conclusion, periodic psychological screening using DASS-Y is essential for the early identification and management of academic burnout in adolescents, supported by sustained psychoeducational programs and professional counseling services.